2010
DOI: 10.1007/dcr.0b013e3181bb869f
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of the Intersphincteric Fistula Tract: An Effective New Technique for Complex Fistulas

Abstract: Ligation of the intersphincteric fistula tract is a new sphincter-sparing procedure for complex transsphincteric fistula. The success rate is comparable with other sphincter-preserving techniques. Importantly, it appeared to effectively preserve continence. Adding safe, muscle-sparing surgical options to our armamentarium for dealing with transsphincteric fistula is essential. Additionally, the procedure is easy to learn and has very low cost. Long-term follow-up and randomized, controlled trials are necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
2
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(129 citation statements)
references
References 16 publications
7
112
2
8
Order By: Relevance
“…Success rates range from 57 to 94% with variable follow-up [12][13][14][15] as shown in Table 1. Overall, a pooled cumulative success rate of 74% can be drawn from this worldwide experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rates range from 57 to 94% with variable follow-up [12][13][14][15] as shown in Table 1. Overall, a pooled cumulative success rate of 74% can be drawn from this worldwide experience.…”
Section: Discussionmentioning
confidence: 99%
“…The initial report in 2006 from Rojanasakul et al [11] showed a 94% healing rate with a 3-month follow-up. Since then, only a few studies of the use of this technique have been reported, mainly published as abstracts, and with variable success rates from 57 to 89% [12][13][14][15]. This intuitive technique is based on the concept of secure closure of the internal opening and concomitant removal of infected cryptoglandular tissue in the intersphincteric plane.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is a relatively new procedure, success rates of 57% and 89% have been reported. 33,34 Long-term follow-up is needed to validate these results, but this operation makes sense as a definitive method of closure of transsphincteric fistulas without sphincterotomy.…”
Section: Fistulotomy With Sphincterotomymentioning
confidence: 99%
“…14 A success rate of 57% to 94.4% was reported for LIFT procedure in various studies. 15,16 This technique prevents the entry of faecal material into the fistula tract and eliminates the formation of septic nidus in the intersphincteric space to allow healing of the anal fistula. The advantages of the LIFT procedure may include preservation of the anal sphincter, minimal tissue injury, shorter healing time and its being a procedure that is relatively easy to perform.…”
Section: Discussionmentioning
confidence: 99%